2016
DOI: 10.5430/elr.v5n1p38
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Iranian EFL Learners’ Self- efficacy Beliefs and Reading Comprehension Ability

Abstract: The aim of the present study was to find out whether language learners' self-efficacy beliefs affect the reading comprehension achievement of EFL learners in Iran. A convenience sample of 120 learners from different language schools participated in this study. A self-efficacy questionnaire was adopted to analyze students' self-efficacy beliefs. To measure their reading comprehension, the reading part of Michigan Test, as a test of English language proficiency was adopted and given to the participants. The Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…It asserted that out of all the psychological variables, self-efficacy is the most substantial predictor of academic success (Bandura, 1977). Also, this finding is in line with numerous past studies (Al Ghraibeh, 2014;Galla et al, 2014;Ghabdian & Ghafournia 2016;Guthrie, Klauda, & Ho 2013;Habibian & Roslan 2014;Hedges & Gable, 2016;Lee & Jonson-Reid, 2016;Naseri & Ghabanchi, 2014;Oh, 2016;Osman et al, 2016;Rachmajanti & Musthofiyah, 2017;Salehi & Khalaji, 2014;Tabrizi & Jafari, 2015;Tobing, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It asserted that out of all the psychological variables, self-efficacy is the most substantial predictor of academic success (Bandura, 1977). Also, this finding is in line with numerous past studies (Al Ghraibeh, 2014;Galla et al, 2014;Ghabdian & Ghafournia 2016;Guthrie, Klauda, & Ho 2013;Habibian & Roslan 2014;Hedges & Gable, 2016;Lee & Jonson-Reid, 2016;Naseri & Ghabanchi, 2014;Oh, 2016;Osman et al, 2016;Rachmajanti & Musthofiyah, 2017;Salehi & Khalaji, 2014;Tabrizi & Jafari, 2015;Tobing, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, few researchers conducted studies on students attending English language learning institutions (Ghabdian & Ghafournia 2016;Piran 2014;Rachmajanti & Musthofiyah 2017). Out of these three studies, only Piran (2014) found an insignificant connection among self-efficacy and reading comprehension.…”
Section: Self-efficacy Beliefs and Reading Comprehensionmentioning
confidence: 99%
“…English teachers and EFL learners in the EFL and ESL context could use the results of the study. Ghabdian and Ghafournia (2016) in their study investigated whether language learners' self-efficacy beliefs affect Iranian EFL learners' reading comprehension ability. The participants of the study were 120 English Language learners from different language schools.…”
Section: Self-efficacymentioning
confidence: 99%
“…Delcourt and Kinzie (1993) stated that perceived self-efficacy reflects an individual's assurance in his or her capability in performing the behavior essential to create particular results. Although brain-based teaching and self-efficacy are two important concepts, a review of the current empirical research on self-efficasy (e.g., Basereh, & Pishkar, 2016;Estonella Mastan, & Maarof, 2014;Ghabdian, & Ghafournia, 2016;Kırmızı, & Dağdeviren Kırmızı, 2015;Mall-Amiri, & Sadeghi, 2014;Yangon Ersanlo, 2015) and brain-based teaching (Demirhan, Önder, & Beşoluk, 2014;Saleh, 2012;Siercks, 2012) indicates that, to date, no study has been carried out to explore the effect of brain-based teaching on self-efficacy which will be the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Research into comprehension revealed that those with higher self-efficacy had higher L2 reading comprehension scores (Burrows 2012;Ghabdian and Ghafournia 2016).…”
Section: Self-efficacy In L2 Readingmentioning
confidence: 99%